2005
DOI: 10.1074/jbc.m500398200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Novel Metallopeptidase MoP112 and Saccharolysin for the Complete Degradation of Proteins Residing in Different Subcompartments of Mitochondria

Abstract: Mitochondria harbor a conserved proteolytic system that mediates the complete degradation of organellar proteins. ATP-dependent proteases, like a Lon protease in the matrix space and m-and i-AAA proteases in the inner membrane, degrade malfolded proteins within mitochondria and thereby protect the cell against mitochondrial damage. Proteolytic breakdown products include peptides and free amino acids, which are constantly released from mitochondria. It remained unclear, however, whether the turnover of malfolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 36 publications
2
74
1
Order By: Relevance
“…In total, of 12 peptides degraded by OOP, 10 also were substrates for PreP. The apparent overlap in the substrate pool between PreP and OOP and the same subcellular localization suggests that these two peptidases might cooperate in vivo for peptide degradation in endosymbiotic organelles, a possibility supported by previous studies in yeast (27).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In total, of 12 peptides degraded by OOP, 10 also were substrates for PreP. The apparent overlap in the substrate pool between PreP and OOP and the same subcellular localization suggests that these two peptidases might cooperate in vivo for peptide degradation in endosymbiotic organelles, a possibility supported by previous studies in yeast (27).…”
Section: Discussionsupporting
confidence: 65%
“…Previous reports suggested that M3A peptidases may be involved in the degradation of targeting peptides and even may cooperate with M16C peptidases (as Cym1 or PreP) in this function (27). We approached this idea by testing the activity of the mitochondria-and chloroplast-resident OOP against the Nicotiana plumbaginifolia pF 1 β, a well-characterized substrate of AtPreP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AtPreP1 and AtPreP2 are dually targeted to both the mitochondrial matrix and chloroplast stroma [14]. The yeast homolog of AtPreP, called MOP112 or CYM1p, appears to be located in the mitochondrial intermembrane space [17] whereas the human homolog (hPreP or MP1) is localized to the mitochondrial matrix and is also known to degrade amyloidbeta peptide (Ab) [18], the toxic agent that accumulates in mitochondria in Alzheimer's disease [19].…”
Section: Introductionmentioning
confidence: 99%